2014
DOI: 10.1007/s13369-014-1331-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Fluid Flow Characteristics of a Laminar Slot Jet on Solid Block Mounted on a Horizontal Surface

Abstract: Numerical simulation is carried out to investigate the flow characteristics of two-dimensional laminar incompressible slot jet flows. Simulations are done for a vertical slot jet on a block at the bottom wall, and the top wall is confined by the parallel surface. The reattachment length, detachment length, vortex center and the coefficient of friction (C f ) are analyzed for different types of flow patterns. The correlation between the Reynolds number (Re) with vortex center and reattachment length is recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The subtle variation of Cf is observed with increasing Re and decreasing AR. From the graph, it is interesting to note, that the peak value of the coefficient of friction decreases with the increase of AR (Muthukannan et al (2014)) (Fig. 18).…”
Section: Effect Of Cf On Solid Blockmentioning
confidence: 93%
See 1 more Smart Citation
“…The subtle variation of Cf is observed with increasing Re and decreasing AR. From the graph, it is interesting to note, that the peak value of the coefficient of friction decreases with the increase of AR (Muthukannan et al (2014)) (Fig. 18).…”
Section: Effect Of Cf On Solid Blockmentioning
confidence: 93%
“…The present authors (Muthukannan et al 2014) conducted a numerical study only on the fluid flow characteristics, of a laminar slot jet on a solid block mounted on a horizontal surface. In their previous research work they found the flow field characteristics for Re ranging from 50 to 300, block height, ranging from 0.25 to 1.0, and block width, ranging from 0.25 to 1.75 as the baseline case of AR5.The previous work has been confined by changing the AR ranging from 2 to 5 as the baseline case of Re 150.…”
Section: Introductionmentioning
confidence: 99%
“…Yan and Saniei [13] considered the heat transfer for an obliquely impinging circular air jet to a flat plate using a preheated wall transient liquid crystal technique. Muthukannan et al [18] investigated numerically the flow characteristics of two-dimensional laminar incompressible slot jet flow for a vertical slot jet on a block at the bottom wall. They investigated the reattachment length, detachment length, vortex center and the coefficient of friction for different types of flow *Sorumlu Yazar (Corresponding Author) e-posta : tamercalisir@gazi.edu.tr patterns.…”
Section: Introductionmentioning
confidence: 99%
“…A strong effect of Reynolds number on size and locations of center of large vortices has been noticed near the lid for the deep cavity flow. [17]carried out Numerical simulations on two-dimensional incompressible slot jet flows. The reattachment length, center of vortex and coefficient of friction (C f ) are analyzed.…”
Section: Introductionmentioning
confidence: 99%